Code-Switching Patterns of English Teachers in an Indonesian Preschool Context: A Case Study at TK Essential Education Bengkulu - Eki Saputra (Edelweiss : Journal Of Innovation In Educational Research, 2026)
This study investigates the patterns and functions of code-switching (CS) employed by English teachers in an Indonesian preschool setting. In the complex linguistic landscape of Bengkulu, where students navigate multiple local dialects alongside the national language, code-switching serves as a vital pedagogical bridge. The present study is a qualitative case study conducted at TK Essential Education Bengkulu during the 2025/2026 academic year. It was designed to explore how teachers utilize tag-switching, inter-sentential, and intra-sentential switching to maximize a restricted 30-minute instructional window for students with zero prior English exposure. The results revealed that: (1) code-switching is a deliberate scaffolding tool that ensures comprehension and maintains emotional security; (2) inter-sentential switching dominates classroom management, while intra-sentential switching is primarily used for vocabulary building; and (3) the integration of local codes (Melayu Bengkulu, Serawai, Rejang) prevents "subtractive multilingualism" and fosters a culturally responsive learning environment. Furthermore, the findings suggest that the strategic use of L1 (First Language) and regional codes accelerates the transition from receptive to productive language skills in early childhood education.